2010
DOI: 10.1016/j.pain.2010.07.028
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, placebo-controlled, double-blind, multiple-crossover study of Fentanyl Pectin Nasal Spray (FPNS) in the treatment of breakthrough cancer pain

Abstract: This randomized, double-blind, crossover study assessed the efficacy and tolerability of a new rapid onset nasal fentanyl formulation (Fentanyl Pectin Nasal Spray; FPNS) for breakthrough cancer pain (BTCP). Eighty-three of 114 patients experiencing one to four BTCP episodes/day while taking ≥60 mg/day of oral morphine or equivalent successfully identified an effective dose of FPNS during a titration phase and entered a double-blind phase in which 10 BTCP episodes were treated with this effective dose (7) or pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
2
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 27 publications
5
112
2
5
Order By: Relevance
“…This is even more relevant when one considers that most patients reported moderate to severe pain at screening. Although efficacy was not studied in this long-term safety study, these findings are in line with the earlier studies that showed FPNS to be consistently effective compared with placebo [16] and IRMS [10].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is even more relevant when one considers that most patients reported moderate to severe pain at screening. Although efficacy was not studied in this long-term safety study, these findings are in line with the earlier studies that showed FPNS to be consistently effective compared with placebo [16] and IRMS [10].…”
Section: Discussionsupporting
confidence: 90%
“…This provides a more reproducible drug delivery with well-controlled peak concentrations and a concentration-time relationship that is consistent with the typical BTCP episode [21]. Two previous randomised, controlled phase III studies have demonstrated that FPNS provides superior pain relief compared with both placebo [16] and immediate-release morphine sulphate (IRMS) [10]. Both studies demonstrated that significant effects on pain could be recorded after 5 min following a dose, and significantly greater clinically meaningful reductions in pain intensity could be seen from 10 min after dosing.…”
Section: Introductionmentioning
confidence: 90%
“…While a previous survey suggested that few patients had prior experience with a nasal route of analgesic medication (Walker et al, 2003), two recent randomized controlled studies of FPNS found that 69-80 % of patients were satisfied or very satisfied with the ease of use and convenience (Portenoy et al, 2010b;Davies et al, 2011b). It should be noted, however, that many of the patients in this "extension study" were pre-selected because of a successful response in the preceding double-blind trials.…”
Section: Discussionmentioning
confidence: 80%
“…After a titration phase to determine the effective dose, the use of INFS at doses of 50 to 200 μg was associated with an onset of activity at 10 min and a more effective treatment of BTcP compared with placebo [24]. In a placebo-controlled, double-blind, crossover study, a pectin formulation of INFS was effective in the treatment of BTcP [25]. The only existing study comparing two different ROOs showed a decrease in pain intensity that was significantly greater with INFS than OTFC from 5 min post-dosing.…”
Section: Rapid-onset Opioidsmentioning
confidence: 99%